Integration of Aeromagnetic Mapping and Audio-Magnetotelluric Data for Groundwater Investigation within the University of Ilorin Main Campus - Abdulazeez, Q. B.; Omolaiye, G. E.; Ajadi, J.; Adam, S. B. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2026)
This study integrates aeromagnetic mapping and audiomagnetotelluric data to investigate subsurface geological structures and assess groundwater potential within the University of Ilorin main campus. The aeromagnetic mapping was processed using several techniques, such as reduction to the equator, regional-residual separation, derivative techniques, and Euler deconvolution, to delineate magnetic lineaments and the structural geology of the study area. The results of this study revealed dominant weak zones in the northern and north-eastern areas and in some parts of the southeastern area of the University of Ilorin Main Campus, which are interpreted as potential groundwater pathways and zones of structural weakness. The 2D audio-magnetotelluric imaging characterized the subsurface resistivity distribution by identifying low-resistivity zones between 0.06 and 1.2 Ωm, associated with weathered and fractured basement aquifers at depths of 40-200 m across several locations. In addition, a selected borehole within the study area validated these interpretations, yielding high discharge rates that confirm the hydraulic significance of the identified conductive horizons. The integrated results highlight that deep-seated fracture zones and weathered layers control groundwater accumulation and yield within the study area. This study demonstrates the effectiveness of combining aeromagnetic and audio-magnetotelluric methods for delineating aquifer systems, which provides a reliable geophysical framework for sustainable groundwater exploration and development within crystalline basement terrains.